Nanometer Fe3O4 mineralized dunaliella salina, preparation method thereof and application of dunaliella salina in construction of microbial fuel cell
By using nano-Fe3O4 mineralized Dunne Salt Algae as anode electropolytic microorganism in microbial fuel cells, the problem of insufficient electrical performance and battery life of microbial fuel cells in the prior art is solved, and more efficient electricity generation and longer Battery life.
Patent Information
- Application Number
- CN202311029120.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
AI Technical Summary
When existing microbial fuel cells use microalgae to produce electricity, there are problems with insufficient power production performance and battery life.
Dunnephrite and nanoFe3O4 were co-cultured in salt algae culture medium, and nanoFe3O4 mineralized Dunnephrite was prepared and applied to the anode of microbial fuel cells to construct dual chamber MFCs.
The power production performance and battery life of microbial fuel cells have been significantly improved. The maximum output voltage of nano-Fe3O4 mineralized salt algae MFC reaches 87.22mV, the stable voltage is 73.61±10mV, and the battery life is 311 hours.
Smart Images

Figure CN119490943A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of microalgae biotechnology and specifically relates to a nano-Fe 3 O 4 Mineralized Dunaliella salina, its preparation method and application in constructing microbial fuel cells. Background Art
[0002] Microbial Fuel Cell (MFC) is a device that directly converts the chemical energy of fuel (such as organic acids, sugars, etc.) into electrical energy with the help of the catalytic action of microorganisms. MFC can generate bioelectricity by decomposing organic matter through electroactive bacteria on the anode. The electroactive bacteria attached to the electrode surface consume nutrients or organic pollutants to produce electrons and protons, and enter the cathode cavity through the circuit and the intermediate membrane to participate in the electrochemical reaction.
[0003] As a biomass fuel, microalgae has attracted attention in the construction of MFC power generation due to its advantages such as high safety and low handling. The microalgae-type MFC, which is a combination of microalgae and MFC, can generate electricity using light energy and carbon dioxide. The electrons generated by the respiration and photosynthesis of algae can be transferred to the electrodes to generate electricity.
[0004] Dunaliella salina is a highly salt-tolerant eukaryotic green algae with no cell wall. It is a photoautotrophic organism that uses water as an electron donor. During photosynthesis, it can grow and reproduce by synthesizing organic matter from simple inorganic substances. It has strong environmental tolerance and can survive in a salinity range of 0.5 to 5 mol / L NaCl. There are two possible uses of using Dunaliella salina to construct MFC: ① storing energy through photosynthesis under light; ② transferring electrons directly to the anode through the photosynthetic electron chain under light.
[0005] In order to meet different needs, it is necessary to modify the microalgae cells or change the culture environment of the microalgae. Summary of the invention
[0006] In order to solve the related technical problems, the primary purpose of the present invention is to provide a nano-Fe 3 O 4 Method for preparing mineralized Dunaliella salina.
[0007] Another object of the present invention is to provide a nano-Fe prepared by the above-mentioned preparation method. 3 O 4 Mineralization of Dunaliella salina.
[0008] Another object of the present invention is to provide the above-mentioned nano-Fe 3 O 4 Application of mineralized Dunaliella salina in the construction of microbial fuel cells.
[0009] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0010] A nano-Fe 3 O 4 The preparation method of mineralized Dunaliella salina is to mix Dunaliella salina cells with nano-Fe 3 O 4 Co-cultured in Dunaliella culture medium to obtain nano-Fe 3 O 4 Mineralization of Dunaliella salina.
[0011] Furthermore, the Dunaliella salina is Dunaliella salina CCAP19 / 18.
[0012] Furthermore, the Dunaliella salina cells are Dunaliella salina cells grown to the logarithmic phase in a Dunaliella culture medium.
[0013] Furthermore, the preparation of the Dunaliella culture medium is as follows: NaNO 3 0.4±0.1g / L, NaH 2 PO 4 ·2H 2 O 0.1 ± 0.1 g / L, NaHCO 3 0.8±0.1g / L, KCl 0.07±0.05g / L, MgSO 4 7H 2 O 1.2±0.1g / L, CaCl 2 ·2H 2 O 0.04±0.05g / L, 0.1% Fe-EDTA solution 0.5mL / L, add A5 trace element solution 1mL / L to the culture medium, adjust the pH to 7.5; the composition of Fe-EDTA solution is as follows: Na 2 EDTA 0.1±0.05g / L, FeCl 3 6H 2 O 0.2±0.1g / L; A5 trace element solution composition is as follows: H 3 BO 3 2±0.5g / L, MnCl 2 ·4H 2 O 1.8±0.1g / L, ZnSO 4 7H 2 O0.2±0.1g / L, CuSO 4 ·5H 2 O 0.08±0.005g / L, (NH 4 ) 6 Mo 7 O24 ·4H 2 O 0.04±0.005g / L; further as follows: NaNO 3 0.420g / L, NaH 2 PO 4 ·2H 2 O 0.156 g / L, NaHCO 3 0.840g / L, KCl 0.074g / L, MgSO 4 7H 2 O 1.230g / L, CaCl 2 ·2H 2 O 0.044g / L, 0.1% Fe-EDTA solution 0.5mL / L, add A5 trace element solution 1mL / L to the culture medium, adjust the pH to 7.5; the composition of Fe-EDTA solution is as follows: Na 2 EDTA 0.189 g / L, FeCl 3 6H 2 O0.244g / L; A5 trace element solution composition is as follows: H 3 BO 3 2.86g / L, MnCl 2 ·4H 2 O 1.81g / L, ZnSO 4 7H 2 O0.22g / L,CuSO 4 ·5H 2 O0.08g / L, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O 0.04g / L.
[0014] The culture conditions are as follows: a temperature of 23±1°C, a light intensity of 3,000±500lx, and a light-dark time ratio of 16h:8h.
[0015] Furthermore, the nano-Fe 3 O 4 The preparation is as follows: 2+ and Fe 3+ Add alkaline solution to the mixed solution of ions, continue stirring at high speed, and co-precipitate to obtain nano-Fe 3 O 4 ; Preferably, 0.99±0.2gFeCl is added to 100mL of water 2 (4H 2 O) and 2.7 ± 0.5 g FeCl 3 (6H 2O), stir until fully dissolved, add 10±1mL 25% NH 4 OH, and then stirred at 20000±5000rpm for 30±5min to obtain nano-Fe 3 O 4 .
[0016] Furthermore, the cell concentration of the Dunaliella salina cells is (0.1-2)×10 7 cells / mL; further (1±0.2)×10 7 cells / mL.
[0017] Furthermore, the nano-Fe 3 O 4 The dispersion concentration is 0.5-8 mg / mL; preferably 2±1 mg / mL.
[0018] Furthermore, the co-culture condition is shaking at 120±20 rpm for 30±5 min.
[0019] A nano-Fe 3 O 4 Mineralized Dunaliella salina is obtained through the above preparation method.
[0020] The above nano-Fe 3 O 4 Application of mineralized Dunaliella salina in the construction of microbial fuel cells.
[0021] Furthermore, the application is to construct a double-chamber MFCs made of organic glass, the anolyte is a culture medium of Dunaliella, and inoculated with nano-Fe 3 O 4 Mineralization of Dunaliella salina, the cathode is potassium persulfate solution; further, the anode liquid is Dunaliella salina culture medium, and inoculated with OD 630 =1.0±0.2 nano-Fe 3 O 4 Mineralized Dunaliella salina, the cathode is 50±5mmol / L potassium persulfate solution; further, the two electrode chambers are separated by a proton exchange membrane Nafion117, and a vacuum pad is sandwiched between the proton exchange membrane and the two electrode chambers to maintain sealing; the cathode and anode are both 24.63cm 2 The circular carbon felt was used as the electrode and was led out with a titanium wire with a diameter of 1 mm and an external resistor of 1 kΩ. All devices were placed in a light incubator with the temperature controlled at 23 ± 1 °C and the light intensity set to 3000 ± 500 lx.
[0022] Technical principle of the present invention: Bionic mineralization of cell surface is a feasible method to artificially construct a shell for cells. The so-called bionic mineralization of cell surface is to deposit a layer of inorganic minerals on the cell surface using the principle of biomineralization. The key is to introduce mineralizing functional groups or molecules into the cell surface under mild conditions, and the core is cell surface modification. Metal oxides have good stability and corrosion resistance. Among them, nano-ferroferric oxide has a large roughness and good biocompatibility, which is conducive to compounding with algae cells. Compared with traditional carbon materials, metal materials have better conductivity and mechanical strength. Therefore, the present invention uses nano-ferroferric oxide to mineralize salt algae, and then construct a microbial fuel cell.
[0023] The present invention takes salt algae as the research object, imitates the strategy of biomimetic mineralization, and realizes the direct and rapid compounding of salt algae with ferroferric oxide nanoparticles. The salt algae compounded with the nanoparticles can be rapidly polymerized.
[0024] The present invention screened different ferroferric oxide concentrations of mineralized salt algae and found that the best mineralization effect could be achieved when the ferroferric oxide nanoparticle concentration was 2 mg / mL.
[0025] The present invention conducted an experiment on encapsulating salt algae with ferroferric oxide nanoparticles and found that the mineralized ferroferric oxide nanoparticles would not destroy the cell structure and had good biocompatibility.
[0026] The present invention adopts salt algae and salt algae mineralized with nano-iron tetroxide as anode power-generating microorganisms to construct a dual-chamber microbial fuel cell MFC. The wild-type salt algae MFC produces electricity stably and is an ideal power-generating microorganism; the MFC constructed with salt algae mineralized with nano-iron tetroxide helps cells to quickly enrich on the electrode surface and improves the power generation performance of the MFC, and the battery life is increased.
[0027] The MFC with Dunaliella DS-Wild as the anode power-producing microorganism has good power generation performance, with a maximum output voltage of 54.76mV, a stable voltage of 47.71±10mV, and a battery life of 274h.
[0028] The MFC with nano-iron oxide mineralized salt algae DS-Wild as the anode power-generating microorganism has good power generation performance, with a maximum output voltage of 87.22mV, a stable voltage of 73.61±10mV, and a battery life of 311h.
[0029] Compared with the prior art, the present invention has the following advantages and effects:
[0030] (1) Dunaliella salina has strong environmental tolerance and can survive in high salt concentrations. During photosynthesis, it can use simple inorganic substances to synthesize organic matter and grow and reproduce. When it is used as an electricity-producing microorganism, MFC produces stable electricity, making it an ideal electricity-producing microorganism.
[0031] (2) Dunaliella culture medium can not only promote the growth of electricity-producing microorganisms, but also serve as the electrolyte of MFC batteries.
[0032] (3)Fe 3 O 4 After mineralization, salt algae can significantly improve the power transmission and production performance and battery life of MFC biobatteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 These are the cultivation pictures of wild-type Dunaliella salina and nano-Fe 4 oxide-mineralized Dunaliella salina; (a) is the algae solution picture of wild-type Dunaliella salina; (b) is the algae solution picture of nano-Fe 4 oxide-mineralized Dunaliella salina.
[0034] Figure 2 These are optical microscope images of wild-type Dunaliella salina and mineralized Dunaliella salina; among them, (a) is a cell image of wild-type Dunaliella salina; (b) is a cell image of nano-iron oxide mineralized Dunaliella salina.
[0035] Figure 3 These are the concentration gradient cell diagrams of the mineralization of nano-iron tetroxide in Dunaliella salina; (a) the cell diagram of wild-type Dunaliella; (b) 0.5 mg / mL, (c) 1 mg / mL, (d) 2 mg / mL, (e) 4 mg / mL, and (f) 8 mg / mL cell diagrams of Dunaliella salina mineralized with nano-iron tetroxide.
[0036] Figure 4 The wild type Dunaliella salina (DS-Wild) and the nano-iron oxide mineralized Dunaliella salina (DS@Fe 3 O 4 )Time-output voltage curve of the MFC constructed. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0038] The experimental methods in the following examples without specific experimental conditions are usually carried out under conventional experimental conditions or the experimental conditions recommended by the manufacturer. The materials and reagents used are commercially available unless otherwise specified.
[0039] Fe 3 O 4 Prepared by chemical coprecipitation method; electrolyte K 2 S 2O 3 , purchased from Tianjin Damao Chemical Reagent Factory (CAS: 7727-21-1); Dunaliella salina, purchased from the Culture Collection of Algae and Protozoa in the UK, number CCAP19 / 18.
[0040] Example 1
[0041] 1. Preparation and cultivation of Dunaliella culture medium
[0042] Preparation of Dunaliella culture medium: NaNO 3 0.420g / L, NaH 2 PO 4 ·2H 2 O 0.156 g / L, NaHCO 3 0.840g / L, KCl 0.074g / L, MgSO 4 7H 2 O 1.230g / L, CaCl 2 ·2H 2 O 0.044g / L, 0.1% Fe-EDTA solution 0.5mL / L. Add 1mL / L of A5 trace element solution to the culture medium and adjust the pH to 7.5.
[0043] The composition of Fe-EDTA solution is as follows: Na 2 EDTA 0.189 g / L, FeCl 3 6H 2 O 0.244g / L.
[0044] The composition of A5 trace element solution is as follows: 3 BO 3 2.86g / L, MnCl 2 ·4H 2 O 1.81g / L, ZnSO 4 7H 2 O0.22g / L,CuSO 4 ·5H 2 O 0.08g / L, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O 0.04g / L.
[0045] Dunaliella cultivation: temperature 23 ± 1 ° C, light intensity 3000 lx, light to dark time ratio 16h: 8h, culture until growth to logarithmic phase (OD 630 =1.0).
[0046] 2. Nano-Fe 3 O 4 Preparation:
[0047] 100 mL of deionized water was heated to 80 °C in an electric furnace. 0.99 g of FeCl 2 (4H 2 O) and 2.7 g FeCl 3 (6H 2 O), continue heating and stirring at high speed until fully dissolved. Quickly add 10mL 25% NH 4 OH, and then continued to stir at 20000 rpm for 30 min in a high-speed stirrer. Fe 3 O 4 The nanoparticles were washed three times with deionized water to a pH of 7, and dried in an oven. Deionized water was added and ultrasonically dispersed again before use.
[0048] 3. Nano-Fe 3 O 4 Preparation of mineralized Dunaliella
[0049] The Dunaliella algae liquid grown to the logarithmic phase was centrifuged at 1000 rpm to remove the Dunaliella culture medium, and then dispersed with fresh Dunaliella culture medium and adjusted to a cell density of 1×10 7 cells / mL. The nano-Fe prepared by chemical co-precipitation 3 O 4 , added to the dispersion of Dunaliella cells, making the nano-Fe 3 O 4 The dispersion concentrations were 0, 0.5, 1, 2, 4, and 8 mg / mL. The cells were shaken at 120 rpm for 30 min before subsequent culture. Cell morphology was photographed at 40X under an optical microscope.
[0050] 4. Construction of MFCs device
[0051] The double-chamber MFCs made of plexiglass were constructed, the anode liquid was Dunaliella culture medium and inoculated with OD 630 =1.0 algae cells, the cathode is potassium persulfate solution (K 2 S 2 O 8 , 50mmol / L). The volume of the anode chamber and cathode chamber is 100mL. The two chambers are separated by a proton exchange membrane (Nafion117). A vacuum pad is sandwiched between the proton exchange membrane and the two chambers to maintain sealing. The cathode and anode are both 24.63cm 2(r = 2.8 cm) circular carbon felt was used as the electrode, and was led out with titanium wire (1 mm in diameter) and connected to an external resistor of 1 kΩ. All devices were placed in a light incubator for the experiment, the temperature was controlled at 23 ± 1 °C, and the light intensity was set to 3 000 lx.
[0052] Control group: The anode liquid was Dunaliella culture medium and inoculated with OD 630 = 1.0 of wild salt algae cells (DS-Wild), the cathode is potassium persulfate solution (K 2 S 2 O 8 , 50mmol / L).
[0053] Experimental group: The anolyte was Dunaliella culture medium and inoculated with OD 630 =1.0 nano-Fe 3 O 4 Mineralized Dunaliella cells (DS@Fe 3 O 4 ), the cathode is potassium persulfate solution (K 2 S 2 O 8 , 50mmol / L).
[0054] Experimental material pretreatment:
[0055] (1) Pretreatment of proton exchange membrane: Nafion117 membrane needs to be pretreated before use in order to achieve better transfer effect. First, boil the membrane in 5% hydrogen peroxide at 80℃ for 1 hour, then soak it in deionized water for 0.5 hour, then boil it in 5% dilute sulfuric acid at 100℃ for 1 hour, and finally soak it in deionized water for 0.5 hour.
[0056] (2) Pretreatment of carbon felt: Soak it in 1 mol / L HCL and acetone for 2 hours respectively, soak it in deionized water for 1 hour to remove surface impurities, and finally dry it for use.
[0057] 5. Analysis method of MFC battery power generation performance
[0058] The voltage signal generated by MFC was automatically collected by a digital multimeter (VICTOR) with a collection frequency of once every 60 seconds and a collection accuracy of 0.01 mV.
[0059] Figure 1 These are the cultivation pictures of wild-type Dunaliella salina and nano-Fe 4 oxide-mineralized Dunaliella salina; (a) is the algae solution picture of wild-type Dunaliella salina; (b) is the algae solution picture of nano-Fe 4 oxide-mineralized Dunaliella salina.
[0060] Figure 2These are optical microscope images of wild-type Dunaliella salina and mineralized Dunaliella salina; among them, (a) is a cell image of wild-type Dunaliella salina; (b) is a cell image of nano-iron oxide mineralized Dunaliella salina.
[0061] Figure 3 These are the concentration gradient cell diagrams of the mineralization of nano-iron tetroxide in Dunaliella salina; (a) the cell diagram of wild-type Dunaliella; (b) 0.5 mg / mL, (c) 1 mg / mL, (d) 2 mg / mL, (e) 4 mg / mL, and (f) 8 mg / mL cell diagrams of Dunaliella salina mineralized with nano-iron tetroxide.
[0062] Figure 4 The wild type Dunaliella salina (DS-Wild) and the nano-iron oxide mineralized Dunaliella salina (DS@Fe 3 O 4 ) The time-output voltage curve of the MFC constructed by . It can be seen that the MFC with wild salt algae cells as the anode electricity-generating microorganisms has good power generation performance, with a maximum output voltage of 54.76mV, a stable voltage of 47.71±10mV, and a battery life of 274 hours; 3 O 4 The MFC with mineralized salt algae cells as anode power-producing microorganisms has better power generation performance, with a maximum output voltage of 87.22mV, a stable voltage of 73.61±10mV, and a battery life of 311 hours.
[0063] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the described embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing nano Fe3O4 mineralized Dunaliella salina, characterized in that: The Dunaliella salina cells and nano-Fe3O4 were co-cultured in a Dunaliella culture medium to obtain nano-Fe3O4 mineralized Dunaliella salina.
2. The method for preparing nano Fe3O4 mineralized Dunaliella salina according to claim 1, characterized in that: The Dunaliella salina cells are Dunaliella salina cells grown to the logarithmic phase in a Dunaliella culture medium; The salt algae culture medium is prepared as follows: NaNO3 0.4±0.1g / L, NaH2PO4·2H2O 0.1±0.1g / L, NaHCO3 0.8±0.1g / L, KCl 0.07±0.05g / L, MgSO4·7H2O 1.2±0.1g / L, CaCl2·2H2O 0.04±0.05g / L, 0.1% Fe-EDTA solution 0.5mL / L, add 1mL / L of A5 trace element solution to the culture medium, and adjust the pH to 7.5; the composition of Fe-EDTA solution is as follows: Na2EDTA 0.1±0.05g / L, FeCl3·6H2O 0.2±0.1g / L; the composition of A5 trace element solution is as follows: H3BO3 2±0.5g / L, MnCl2·4H2O 1.8±0.1g / L, ZnSO4·7H2O 0.2±0.1g / L, CuSO4·5H2O0.08±0.005g / L, (NH4)6Mo7O 24 4H2O 0.04±0.005g / L; The preparation of the nano-Fe3O4 is as follows: 2+ and Fe 3+ An alkaline solution is added to the mixed solution of ions, and the mixture is stirred at a high speed continuously to co-precipitate nano-Fe3O4.
3. The method for preparing nano Fe3O4 mineralized Dunaliella salina according to claim 2, characterized in that: The salt algae culture medium is prepared as follows: NaNO3 0.420g / L, NaH2PO4·2H2O 0.156g / L, NaHCO3 0.840g / L, KCl 0.074g / L, MgSO4·7H2O 1.230g / L, CaCl2·2H2O 0.044g / L, 0.1% Fe-EDTA solution 0.5mL / L, add A5 trace element solution 1mL / L to the culture medium, and adjust the pH to 7.5; the Fe-EDTA solution composition is as follows: Na2EDTA 0.189g / L, FeCl3·6H2O 0.244g / L; the A5 trace element solution composition is as follows: H3BO3 2.86g / L, MnCl2·4H2O 1.81g / L, ZnSO4·7H2O 0.22g / L, CuSO4·5H2O 0.08g / L, (NH4)6Mo7O 24 4H2O0.04g / L; The culture conditions are as follows: temperature of 23±1°C, light intensity of 3000±500lx, and light-dark time ratio of 16h:8h; The preparation of the nano-Fe3O4 is as follows: 0.99±0.2g FeCl2(4H2O) and 2.7±0.5g FeCl3(6H2O) are added to 100mL of water, stirred until fully dissolved, 10±1mL 25% NH4OH is added, and stirring is continued at 20000±5000rpm for 30±5min to coprecipitate to obtain nano-Fe3O4.
4. The method for preparing nano Fe3O4 mineralized Dunaliella salina according to claim 1, characterized in that: The cell concentration of the Dunaliella salina cells is (0.1-2)×10 7 cells / mL; The dispersion concentration of the nano Fe3O4 is 0.5-8 mg / mL.
5. The method for preparing nano Fe3O4 mineralized Dunaliella salina according to any one of claims 1 to 4, characterized in that: The cell concentration of the Dunaliella salina cells is (1±0.2)×10 7 cells / mL; The dispersion concentration of the nano-Fe3O4 is 2±1 mg / mL; The co-culture condition is shaking at 120±20 rpm for 30±5 min.
6. The method for preparing nano Fe3O4 mineralized Dunaliella salina according to any one of claims 1 to 4, characterized in that: The Dunaliella salina is Dunaliella salina CCAP19 / 18.
7. A nano-Fe3O4 mineralized Dunaliella salina, characterized by: The method is obtained by the preparation method described in any one of claims 1 to 6.
8. Use of the nano-Fe3O4 mineralized Dunaliella salina described in claim 6 in constructing a microbial fuel cell.
9. The use according to claim 8, characterized in that: The application is: constructing double-chamber MFCs made of organic glass, the anode liquid is salt algae culture medium, and is inoculated with nano-Fe3O4 mineralized Dunaliella salina, and the cathode is potassium persulfate solution.
10. The use according to claim 8, characterized in that: The application is to construct a double-chamber MFC made of organic glass, the anode liquid is a culture medium of Dunaliella, and the OD 630 =1.0±0.2 nano-Fe3O4 mineralized Dunaliella salina, the cathode is 50±5mmol / L potassium persulfate solution; the two electrode chambers are separated by a proton exchange membrane Nafion117, and a vacuum pad is sandwiched between the proton exchange membrane and the two electrode chambers to maintain sealing; the cathode and anode are both 24.63cm 2 The circular carbon felt was used as the electrode and was led out with a titanium wire with a diameter of 1 mm and an external resistor of 1 kΩ. All devices were placed in a light incubator with the temperature controlled at 23 ± 1 °C and the light intensity set to 3000 ± 500 lx.
Citation Information
Patent Citations
Green algae biological fuel cell generating power on basis of photosynthesis
CN102075113A
Enzyme biological fuel cell electrodes and application in manufacture of double-room enzyme biological fuel cell
CN103066305A
Phycomycetes microbial fuel cell and preparation method and application of phycomycetes microbial fuel cell
CN103427102A
Marine microalgae strain and application thereof
CN107164271A
Dunaliella salina absorption composite tin simple substance electrode and preparation method thereof
CN112909230A